Psychology and COVID-19: impacts, themes and way forward. (June 2020) - Pillay, Anthony L; Barnes, Brendon R
COVID-19 has brought a new set of challenges at a time when poorer nations were struggling with existing burdens. However, the lockdown restrictions aimed at slowing the infection rate has created problems of their own such as increased unemployment, poverty, and mental health problems. While the lockdown approach may be effective for public health, there is concern about the way it is formulated, the empirical basis of some restrictions, and societal impacts. There is additional concern that COVID-19 and associated restrictions disproportionately affect marginalised groups. As a discipline primarily concerned with human behaviour, Psychology has much to contribute to addressing the pandemic.